WHAT TO LEARN FROM PREDONATION DEFERRAL OF BLOOD DONORS? - DR.GARGADE CHITRAWATI B.,; DR.DESHPANDE RANGRAO H., (International Journal of Pharma and Bio Sciences, 2016)
Blood cannot be manufactured-it can only come from generous blood donors. In an attempt to ensure a safe blood supply, there are strict controls on who may donate. There is a serious mismatch between demand and availability of blood in the country. The study was conducted retrospectively at a rural medical college in the Konkan area of Maharashtra. All those who deferred from blood donation between 1st January 2013 and 30th Nov 2015 were included in the study. Total deferral rate was 4.6%, with 30 % permanent deferrals and 70% temporary deferrals. Study of predonation deferral pattern may be helpful to know the health status of the general population and blood loss because of temporary deferrals can be minimized by providing health facilities and educating the population about their temporary deferral status.